Regional Original Revenue, Government Expenditure, and Investment in Relation to Economic Growth in West Sulawesi - Ishaka, Faika Kadriana; Arifuddin, ‎; Hanafi, Kartini; Yamin, Muhammad; Azhar, Ahmad Nurzaki (KnE Social Sciences, 2025)
Economic growth is a process in which a country’s economic conditions continuously change into conditions perceived as better over a specific period. This study aims to demonstrate the influence of local revenue, regional expenditure, and investment on economic growth in West Sulawesi. The research method employs a descriptive quantitative approach. The population and sample use are saturated or total sampling of time series data from 2017 to 2022, calculated weekly. Data analysis uses path analysis. The results show a direct influence between exogenous and endogenous variables. Local revenue and regional expenditure positively but insignificantly affect economic growth. The contribution of local revenue to the total regional budget is small compared to balanced funds or other sources, resulting in a minor impact on economic growth. The positive but insignificant regional expenditure is due to its potential contribution, which has not yet been optimized. This condition can be addressed by improving efficiency, designing more productive spending, and directing the budget to strategic sectors with both direct and long-term impacts on the regional economy. Meanwhile, investment negatively and significantly affects economic growth. This indicates that increased investment is associated with a decline in economic growth, reflecting inefficiencies, misaligned investment directions, or structural challenges in optimizing investments.